Bone health in children with long-term idiopathic subclinical hypothyroidism - Di Mase Raffaella; Cerbone Manuela; Improda Nicola; Esposito Andrea; Capalbo Donatella; Mainolfi Ciro; Santamaria Francesca; Pignata Claudio; Salerno Mariacarolina (BMC, 2012)
Abstract Background Subclinical hypothyroidism (SH) is a relatively common condition characterized by a mild persistent thyroid failure. The management of children with SH is still a controversial issue and the decision to treat with L-thyroxine represents a clinical dilemma. Thyroid hormone and TSH play an important role in skeletal growth and bone mineral homeostasis. Aim To evaluate whether untreated idiopathic SH may affect bone health in childhood and to compare two different diagnostic tools such as dual-energy X-ray densitometry (DXA) and quantitative ultrasound (QUS). Patients and Methods Twenty-five children and adolescents (11 males) aged 9.8 ± 3.5 years (range 4.2-18.7) with untreated idiopathic SH were enrolled in the study. SH was diagnosed on the basis of normal FT4 levels with TSH concentrations between 4.2 and 10 mU/l. Children have been followed for 3.3 ± 0.3 years from the time of SH diagnosis. Twenty-five healthy children, age- and sex-matched, were enrolled as controls. Patients and controls underwent DXA to evaluate lumbar spine bone mineral density (BMD) and QUS at proximal phalanges of the non-dominant hand to assess bone quality, measured as amplitude-dependent speed of sound (Ad-SoS) and bone transmission time (BTT). Results Mean BMD Z-score was −0.4 ± 1.36 in patients and −0.2 ± 1.2 in controls. Mean Ad-SoS Z-score was 0.01 ± 1.0 in patients and 0.1 ± 1.2 in controls and mean BTT Z-score was −0.03 ± 0.8 and 0.04 ± 1.1 respectively. All values were within the normal range, both in patients and in controls. There were no statistically significant differences between the two groups. Conclusion Bone health, evaluated by lumbar spine DXA and phalangeal QUS, is not impaired in our children, despite long-term duration of idiopathic SH. Data about bone status provided by QUS are comparable to those provided by DXA. Therefore, QUS may represent a good, cheaper and safe screening test for bone evaluation in children with SH.